Can a Conversation Between Mesenchymal Stromal Cells and Macrophages Solve the Crisis in the Inflamed Intestine? - Hidalgo-Garcia, Laura; Galvez, Julio; Rodriguez-Cabezas, M. Elena; Anderson, Per O. (Frontiers in Pharmacology, 2018)
Inflammatory bowel disease (IBD) is a group of chronic inflammatory conditions of the gastrointestinal tract characterized by an exacerbated mucosal immune response. Macrophages play pivotal roles in the maintenance of gut homeostasis but they are also implicated in the pathogenesis of IBD. They are highly plastic cells and their activation state depends on the local environment. In the healthy intestine, resident macrophages display an M2 phenotype characterized by inflammatory anergy, while inflammatory M1 macrophages dominate in the inflamed intestinal mucosa. In this regard, modifying the balance of macrophage populations into an M2 phenotype has emerged as a new therapeutic approach in IBD. Multipotent mesenchymal stromal cells (MSCs) have been proposed as a promising cell-therapy for the treatment of IBD, considering their immunomodulatory and tissue regenerative potential. Numerous preclinical studies have shown that MSCs can induce immunomodulatory macrophages and have demonstrated that their therapeutic efficacy in experimental colitis is mediated by macrophages with an M2-like phenotype. However, some issues have not been clarified yet, including the importance of MSC homing to the inflamed colon and/or lymphoid organs, their optimal route of administration or whether they are effective as living or dead cells. In contrast, the mechanisms behind the effect of MSCs in human IBD are not known and more data are needed regarding the effect of MSCs on macrophage polarization that would support the observation reported in the experimental models. Nevertheless, MSCs have emerged as a novel method to treat IBD that has already been proven safe and with clinical benefits that could be administered in combination with the currently used pharmacological treatments.